Contemporary management of high-grade renal trauma: Results from the American Association for the Surgery of Trauma Genitourinary Trauma study. Issue 3 (March 2018) - Keihani, Sorena; Xu, Yizhe; Presson, Angela P.; Hotaling, James M.; Nirula, Raminder; Piotrowski, Joshua; Dodgion, Christopher M.; Black, Cullen M.; Mukherjee, Kaushik; Morris, Bradley J.; Majercik, Sarah; Smith, Brian P.; et al.
Abstract : BACKGROUND: The rarity of renal trauma limits its study and the strength of evidence-based guidelines. Although management of renal injuries has shifted toward a nonoperative approach, nephrectomy remains the most common intervention for high-grade renal trauma (HGRT). We aimed to describe the contemporary management of HGRT in the United States and also evaluate clinical factors associated with nephrectomy after HGRT. METHODS: From 2014 to 2017, data on HGRT (American Association for the Surgery of Trauma grades III-V) were collected from 14 participating Level-1 trauma centers. Data were gathered on demographics, injury characteristics, management, and short-term outcomes. Management was classified into three groups—expectant, conservative/minimally invasive, and open operative. Descriptive statistics were used to report management of renal trauma. Univariate and multivariate logistic mixed effect models with clustering by facility were used to look at associations between proposed risk factors and nephrectomy. RESULTS: A total of 431 adult HGRT were recorded; 79% were male, and mechanism of injury was blunt in 71%. Injuries were graded as III, IV, and V in 236 (55%), 142 (33%), and 53 (12%), respectively. Laparotomy was performed in 169 (39%) patients. Overall, 300 (70%) patients were managed expectantly and 47 (11%) underwent conservative/minimally invasive management. Eighty-four (19%) underwent renal-related open operative management with 55 (67%) of them undergoing nephrectomy. Nephrectomy rates were 15% and 62% for grades IV and V, respectively. Penetrating injuries had significantly higher American Association for the Surgery of Trauma grades and higher rates of nephrectomy. In multivariable analysis, only renal injury grade and penetrating mechanism of injury were significantly associated with undergoing nephrectomy. CONCLUSION: Expectant and conservative management is currently utilized in 80% of HGRT; however, the rate of nephrectomy remains high. Clinical factors, such as surrogates of hemodynamic instability and metabolic acidosis, are associated with nephrectomy for HGRT; however, higher renal injury grade and penetrating trauma remain the strongest associations. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III; Therapeutic study, level IV.